2017
DOI: 10.31018/jans.v9i3.1369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid and nutrients mixture on quality parameter of Tomato (Lycopersicon esculentum Mill.) under polyhouse condition

Abstract: An experiment was conducted on Effect of humic acid and nutrients mixture on growth and yield parameter of Tomato (Lycopersicon esculentum Mill.) under polyhouse condition at Rajasthan College of Agriculture, Udaipur (Raj.). The data was analyzed statistically following completely randomized design. The results revealed that treatment T7 [(RDF + humic acid 10 kg/ha soil application + humic acid 0.1% foliar spray + nutrient mixture foliar spray (0.2% Ca + 0.5% Mg + 0.2% B + 0.5% Zn)] was recorded superior to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
5
4
0
Order By: Relevance
“…However, for early yield trait the treatments 1, 2 and 3 g L -1 of HA did not significantly different from each other, in the second season. These results reflect a general agreement with those obtained by Kumar et al (2017) and Jayasinghe and Weerawansha (2018) on tomato plants. While these results did not agree with De Lima et al (2011), who did not find a significant effect of adding of tomato plants with humic acid on the characteristics of the crop and its Enhancing the Productivity and Quality of Tomato using Magnetized Water and Humic Acid as Bio-stimulant Agents quality, except for the T.S.S.…”
Section: Ripe Fruit Yield and Its Componentssupporting
confidence: 93%
See 2 more Smart Citations
“…However, for early yield trait the treatments 1, 2 and 3 g L -1 of HA did not significantly different from each other, in the second season. These results reflect a general agreement with those obtained by Kumar et al (2017) and Jayasinghe and Weerawansha (2018) on tomato plants. While these results did not agree with De Lima et al (2011), who did not find a significant effect of adding of tomato plants with humic acid on the characteristics of the crop and its Enhancing the Productivity and Quality of Tomato using Magnetized Water and Humic Acid as Bio-stimulant Agents quality, except for the T.S.S.…”
Section: Ripe Fruit Yield and Its Componentssupporting
confidence: 93%
“…A gradual significant increase in the values was also observed with each increase in the humic acid (HA) concentrate, as shown Enhancing the Productivity and Quality of Tomato using Magnetized Water and Humic Acid as Bio-stimulant Agents in Fig 10 . The enhanced effects of addition of HA on tomato plants were also obtained by Kazemi (2013). These results reflected similar trends to those reported by Husein and Abou El-Hassan, (2015) and Kumar et al (2017), on tomato. Generally, these authors found that tomato plants responded to different magnetic water and adding of humic acid, were recognized as a vital step in stepping up the fruit yield quality.…”
Section: Chemical Composition Of Rip Fruitsupporting
confidence: 92%
See 1 more Smart Citation
“…Both species are broad generalists that are widely distributed throughout the tropics (Engel 2007), and both were observed visiting all four crop species. These findings reflect those of (Kumar et al 2017), who found that blue-banded bees visited Solanum melongena (eggplant), Capsicum frutescens (Chili), and Solanum lycopersicum (tomatoes). Notably, many solanaceous crops are dependent on insect pollinators for sufficient yield (Kumar et al 2017).…”
Section: Wild Bee Abundancesupporting
confidence: 88%
“…These findings reflect those of (Kumar et al 2017), who found that blue-banded bees visited Solanum melongena (eggplant), Capsicum frutescens (Chili), and Solanum lycopersicum (tomatoes). Notably, many solanaceous crops are dependent on insect pollinators for sufficient yield (Kumar et al 2017).…”
Section: Wild Bee Abundancesupporting
confidence: 88%